Sphenopalatine artery surgery for refractory idiopathic epistaxis: Systematic review and meta‐analysis. (6th January 2019) - Kitamura, Takahiro; Takenaka, Yukinori; Takeda, Kazuya; Oya, Ryohei; Ashida, Naoki; Shimizu, Kotaro; Takemura, Kazuya; Yamamoto, Yoshifumi; Uno, Atsuhiko
Abstract : Objectives: Epistaxis, especially posterior epistaxis, is occasionally refractory to treatment. In these cases, sphenopalatine artery surgeries, including cauterization and ligation, are required. Previous reports have demonstrated treatment results for these procedures but failed to provide high‐level evidence. The aim of this study was to quantify the rates of failure and perioperative complications of these procedures by using a meta‐analysis technique. Methods: We systematically searched electronic databases and identified articles regarding epistaxis, sphenopalatine artery ligation, or cauterization. Pooled rebleeding and complication rates were calculated by using a random effects model. Results: A total of 896 cases of sphenopalatine ligation or cauterization for epistaxis were analyzed. Pooled rebleeding rates for the entire cohort, cauterization group, and ligation group were 13.4% (95% confidence interval [CI] 10.0–17.8, P < 0.001), 7.2% (95% CI 4.6–11.0, P < 0.001), and 15.1% (95% CI 9.8–22.5, P < 0.001), respectively. Pooled perioperative complication rates for the entire cohort, cauterization group, and ligation group were 8.7% (95% CI 4.9–15.1, P < 0.001), 10.2% (95% CI 3.8–24.5, P < 0.001), and 6.4% (95% CI 1.8–20.9, P < 0.001), respectively. Conclusion: Overall, sphenopalatine surgery for refractory epistaxis is an effective method because of its low rates of failure and complications. Cauterization is more effective than ligation, whereas complications are comparable between the two procedures. Laryngoscope, 129:1731–1736, 2019